2019
DOI: 10.1111/jocd.12919
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of activated platelet‐rich plasma supernatant promotion of hair growth by cultured dermal papilla cells

Abstract: Summary Background Platelet‐rich plasma (PRP) is an innovative treatment of androgenic alopecia in the early stages of development, and its mechanism of action is not well investigated. Objective The objective was to investigate the promotion of hair growth by activated PRP supernatant in cultured dermal papilla cells (DPCs). Methods and Materials Human DPCs were isolated and grown in culture with or without activated PRP supernatant. The expression of phosphorylated growth factor receptors (GFRs) in cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 24 publications
0
15
0
1
Order By: Relevance
“…Damage to or the absence of skin appendages not only delays wound healing but also leads to incomplete skin function and scar outcomes [ 43 ]. There have been clinical cases of PRP used in the treatment of alopecia [ 44 , 45 ], and further in-depth research found that it could affect the hair growth cycle and is beneficial to hair follicle reconstruction [ 46 , 47 ]. Interestingly, the hair follicles and sebaceous glands were distributed in the newborn skin in the PRP group on day 14, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to or the absence of skin appendages not only delays wound healing but also leads to incomplete skin function and scar outcomes [ 43 ]. There have been clinical cases of PRP used in the treatment of alopecia [ 44 , 45 ], and further in-depth research found that it could affect the hair growth cycle and is beneficial to hair follicle reconstruction [ 46 , 47 ]. Interestingly, the hair follicles and sebaceous glands were distributed in the newborn skin in the PRP group on day 14, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IGF2R as a target gene of miR-211 activates the MAPK signaling pathway and thereby inhibits the formation of skin melanoma ( Dror et al, 2016 ). MAPK is also a signaling pathway for hair follicle growth and development and IGF2R may also affect hair color and hair follicle growth through this signal pathway ( Xiao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regulators in the MAPK signaling pathway and other hairy-related genes translated into a cyclic wave of expression and serves as a positional cue for FGF signaling pathway (a vital regulatory factor that regulates the periodic changes of hair follicles) through Notch signaling pathway (key member in the differentiation and maturation of hair follicles) [ 33 , 40 , 41 ]. Especially the activated MAPK signaling could act as positive signaling to promote dermal papilla cell proliferation, which is an important factor for the formation of hair curvature [ 4 , 42 ]. In addition, mTOR signaling pathway is a regulator of dermal papilla cells leading to multiple papillary centers (MPC) formation to cause the phenotype of wool curvature [ 4 ].…”
Section: Discussionmentioning
confidence: 99%